2017
DOI: 10.1039/c7tb01142c
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced cell uptake of fluorescent drug-loaded nanoparticles via an implantable photothermal fibrous patch for more effective cancer cell killing

Abstract: Great efforts have been devoted to effective delivery of therapeutics into cells for cancer therapy. The exploration of nanoparticle based drug delivery systems (DDSs) faces daunting challenges in low efficacy of intracellular delivery. Herein, a localized drug delivery device consisting of photoluminescent mesoporous silica nanoparticles (PLMSNs) and photothermal fibrous matrix was investigated. Specifically, PLMSNs modified with a pH-sensitive polydopamine (PDA) ‘gatekeeper’ served as a doxorubicin (DOX) car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 45 publications
(43 reference statements)
0
7
0
Order By: Relevance
“…Compared to drug administrations in the free form, the implant was seen to significantly enable a superior cell uptake effect, thus increasing the drug efficacy against tumor cells by responding to under-near-infrared irradiation. The photothermal effect of the carbon nanotubes weakened the electrostatic interaction between the photoluminescent nanocarriers and the PCL/gelatin nanofibers, resulting in the controlled release and, subsequently, internalization of DOX for a more effective cancer cell killing action [243].…”
Section: Implantablementioning
confidence: 99%
“…Compared to drug administrations in the free form, the implant was seen to significantly enable a superior cell uptake effect, thus increasing the drug efficacy against tumor cells by responding to under-near-infrared irradiation. The photothermal effect of the carbon nanotubes weakened the electrostatic interaction between the photoluminescent nanocarriers and the PCL/gelatin nanofibers, resulting in the controlled release and, subsequently, internalization of DOX for a more effective cancer cell killing action [243].…”
Section: Implantablementioning
confidence: 99%
“…Some researchers believe that NPs can accumulate within tumors due to the EPR effect while avoiding most normal cells [41,56]. Passively targeted NPs can be specifically designed as a result of the EPR effect [20,37,[57][58][59]. Although the passive targeting technique is clinically accepted, it has numerous limitations, such as inefficient NP/drug diffusion, the random nature of NP circulation in the blood prior to reaching the tumor environment, and the fact that some tumors do not display an EPR effect, and the penetrability of vessels are unlikely to be uniform in a single tumor [53,55,60,61].…”
Section: Systemic Delivery Routesmentioning
confidence: 99%
“…The synthesis of ZGOC nanofibers was performed using via the modified a modified protocol based on previous studies reported in the literature. [52][53][54] The electrospinning precursor was prepared by a standard sol-gel approach. Ga(NO3)3•xH2O (0.475 g), Zn(NO3)3•6H2O (0.279 g) and Cr(NO3)3•9H2O (0.002 g) were added to 2 mL deionized water 6 mL ethanol and 3 mL N,N-dimethylformamide (DMF) and mixed well by stirring for 1 h. Subsequently, 0.7 g PVP was added and stirred for further 3 h to obtain a homogeneous solution.…”
Section: Synthesis Of Zgoc Nanofibersmentioning
confidence: 99%